2016
DOI: 10.1371/journal.pcbi.1005211
|View full text |Cite
|
Sign up to set email alerts
|

As Simple As Possible, but Not Simpler: Exploring the Fidelity of Coarse-Grained Protein Models for Simulated Force Spectroscopy

Abstract: Mechanical unfolding of a single domain of loop-truncated superoxide dismutase protein has been simulated via force spectroscopy techniques with both all-atom (AA) models and several coarse-grained models having different levels of resolution: A Gō model containing all heavy atoms in the protein (HA-Gō), the associative memory, water mediated, structure and energy model (AWSEM) which has 3 interaction sites per amino acid, and a Gō model containing only one interaction site per amino acid at the Cα position (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 92 publications
0
31
0
Order By: Relevance
“…al. 23 recently demonstrated that three different CG models provide disparate descriptions of the forced unfolding process of a 110 residue peptide, despite the capability of all models to fold the peptide to the proper native structure. Furthermore, the fidelity of the folding process, with respect to an AA reference simulation, did not correlate with the complexity of the model.…”
Section: Introductionmentioning
confidence: 99%
“…al. 23 recently demonstrated that three different CG models provide disparate descriptions of the forced unfolding process of a 110 residue peptide, despite the capability of all models to fold the peptide to the proper native structure. Furthermore, the fidelity of the folding process, with respect to an AA reference simulation, did not correlate with the complexity of the model.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have analyzed the force--induced mechanical unfolding of a de novo designed SOD1 construct . (39) , obtained by truncating the metal---binding loops (40). In silico methods have also been successfully used to design mutants of β2---microglobulin by changing surface residues to modulate its intrinsic solubility (41).…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Although these models have been useful for investigating the environment-dependent folding processes of IDPs 27,28 (i.e., coupled folding and binding processes), their reliance on a well-defined native structure limits their ability to describe unfolded or disordered conformations. This limitation can even propagate into the characterization of the folding process of globular proteins, resulting in a qualitatively incorrect representation of folding pathways 29 .…”
Section: Introductionmentioning
confidence: 99%